Comparative proteome profiling of bovine and human Staphylococcus epidermidis strains for screening specifically expressed virulence and adaptation proteins. Issue 16 (10th July 2014) - Siljamäki, Pia; Varmanen, Pekka; Kankainen, Matti; Pyörälä, Satu; Karonen, Taru; Iivanainen, Antti; Auvinen, Petri; Paulin, Lars; Laine, Pia K.; Taponen, Suvi; Simojoki, Heli; Sukura, Antti; et al.
<x xml:space="preserve">Abstract</x> The present study reports a comparative proteome cataloging of a bovine mastitis and a human‐associated Staphylococcus epidermidis strain with a specific focus on surfome (cell‐wall bound and extracellular) proteins. Protein identification by 1DE coupled with LC‐MS/MS analyses resulted in 1400 and 1287 proteins from the bovine (PM221) and human (ATCC12228) strains, respectively, covering over 50% of all predicted and more than 30% of all predicted surfome proteins in both strains. Comparison of the identification results suggests elevated levels of proteins involved in adherence, biofilm formation, signal transduction, house‐keeping functions, and immune evasion in PM221, whereas ATCC12228 was more effective in expressing host defense evasion proteases, skin adaptation lipases, hemagglutination, and heavy‐metal resistance proteins. Phenotypic analyses showed that only PM221 displays protein‐ and DNA‐mediated adherent growth, and that PM221 was more efficient in cleaving tributyrin, a natural compound of milk fat under low CO2 conditions. These findings are in line with the identification data and suggest that distinct expression of lipases and adhesive surfome proteins could lead to the observed phenotypes. This study is the first extensive survey of S. epidermidis proteomes to date, providing several protein candidates to be examined for their roles in adaptation and virulence in vivo. All MS data have been deposited in the ProteomeXchange with identifier PXD000404 (http://proteomecentral.proteomexchange.org/dataset/PXD000404).